TINJAUAN KARAKTERISTIK BEBERAPA GEMPA BESAR - Tamboto, Winny J.; Windah, Reky Stenly (Sam Ratulangi University, 2012)
A response spectrum is a plot of the peak values of the response (displacement, velocity, or acceleration) of a number of SDOF systems with different natural vibration periods subjected to the same seismic input. Therefore, an acceleration response spectrum represents the peak accelerations that a suite of SDOF systems with a range of natural periods may exhibit when subject to a given ground motion component.In general, the acceleration response spectrum associated with a specific time-history recorded at a given location has a jagged shape with significant peaks and valleys. The response spectrum for another ground motion recorded at the same site during a different earthquake will exhibit also an irregular shape, but the peaks and valleys will not necessarily coincide with those in the previous one. Therefore, appropriately smoothed spectra are usually defined for design and evaluation purposes. These spectra are termed design response spectra. They do not represent the particular acceleration response from a single ground motion time-history, but rather they are intended to be more representative of general characteristics for a reasonable range of expected ground motions at a given site.Keywords: response spectrum, SDOF system, time-history, ground motions